Automation and the Welfare State: Technological Change as a Determinant of Redistribution Preferences. (February 2019) - Thewissen, Stefan; Rueda, David
Technological change is widely considered to be a key driver of the economic and occupational structure of affluent countries. Current advances in information technology have led to a significant substitution of routine work by capital, while occupations with abstract or interpersonal manual task structures are complemented or unaffected. We develop a simple theoretical framework for the reasons why individuals in routine task-intensive occupations would prefer public insurance against the increased risk of future income loss resulting from automation. Moreover, we contend that this relation will be stronger for richer individuals who have more to lose from automation. We focus on the role of occupational elements of risk exposure and challenge some general interpretations of the determinants of redistribution preferences. We test the implications of our theoretical framework with survey data for 17 European countries between 2002 and 2012. While up to now the political economy literature has emphasized other occupational risks, we find vulnerability to automation to be an important determinant of the demand for redistribution that should not be ignored.